Utilization of Low Priced Fish for Preparation of Noodles - Jyoti, Kumari; Sudhakara, N. S.; Gupta, Vipul (Fishery Technology, 2020)
The present investigation aimed at utilization of deep sea fish species viz., reef cod (Epinephelus dicanthus), locally called murami for the preparation of noodles. The fish was subjected to mechanical deboning to collect minced meat which was incorporated in noodles at levels 5, 10, 15, 20, 25 and 30%. Noodles without fish mince was kept as control and quality of the prepared noodles were determined. Out of these three samples namely one batch of control and two batches of fish noodles with 15 and 20% fish mince were packed in retortable pouch. Effect of different levels of reef cod mince on the sensory quality like appearance, color, odour, taste, texture, firmness, chewiness, cooking characteristics like cooking time, cooking loss, swelling index, water absorption, color and proximate composition were evaluated. With regard to thickness, the control was thinner than fish noodles. The noodle strands were smooth in batches 5 to 20% and hence required less time for cooking compared to control whereas noodles with 25% and 30% mince needed longer cooking time. The swelling indices were lower in fish noodles compared to control with the exception of sample with 5 and 25% mince. The cooking loss increased in fish noodles compared to control noodles. The water absorption capacity of fish noodles was found to be lower than that of control as indicated by a decrease in the L* value. Addition of mince appeared to have no significant effect on the yellowness of the noodles. The protein content increased significantly with the increase in the percentage of fish mince, but this increase was not proportional which can be attributed to the variation in moisture content of noodles. With regard to sensory quality, the control was superior. Firmness and chewiness showed lower values at higher fish mince levels.